Sosialisasi Peran Penting Masyarakat dalam Mewujudkan Birokrasi Bersih dan Anti Korupsi Melalui Kesadaran Kolektif di Desa Landbaw Kecamatan Gisting Kabupaten Tanggamus - Ulil Albab; Dwiyan Kurniawan; Yuniarti Yuniarti; Nurul Afifah Yuliana; Citra Kurnia Dewi (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to identify and analyze the role of the community in encouraging a clean and perception-free bureaucracy through collective awareness in Landbaw Village, Gisting District, Tanggamus Regency. This service is carried out through participatory methods, including counseling and outreach involving village officials and the community. The research results show that increasing collective community awareness can support the realization of a more transparent and accountable bureaucracy, as well as strengthening collaboration between the community and village officials.